CAKUPAN PENIMBANGAN ANAK BALITA DI INDONESIA - Sandjaja Sandjaja; Titiek Setyowati; Sudikno Sudikno (Persagi, 2005)
ABSTRACTBackground: Monthly weighing session in Posyandu is an important activity for growth monitoring and promotion escpecially for children below five years old. By knowing weight every month, growth trajectory can be assessed and nutrition intervention and education can be applied. However, there has been a tendency of decreasing coverage of Posyandu in Indonesia during recent years. Objectives: To determine the coverage of children below five years old attending Posyandu or other weghing post. Methods: Data used for the analysis was from Susenas Modul (VSEN.2004.MPK). Samples were children aged 0 – 59 months weighted in Posyandu or other weighing post one month prior to data collection. Analysis of weighing coverage was based on some variables including province, urban rural area, age of children, frequency of visit to health facilities, and household expenditur. Results: Out of a total 21,932 children included in the analysis, 50.4% attended Posyandu or other weighing session, 47.9% not attended, and 2.1% did not know. The figure was lower than the target of 80% coverage set by MOH. The coverage varied among provinces, the lowest was found in North Sumatra (29.6%) and the highest in DI Yogjakarta (77.3%). The coverage was higher in urban areas (56.9%) than that in rural areas (45.3%). There was a trend of decreasing coverage by increasing age of children. The coverage of weighing participation of babies aged less than 6 months old was 68.2% and continued to decrease especially after the age of 24 months old to only 33.0% among children aged 48 months old or older. Poor families was more likely to have lower coverage (47.4%) than families of high socio economic status (60.1%). Conclusion: High coverage of children under five years old attending weighing session in Posyandu was found in certain province (DI Yogjakarta), urban areas, younger children, better health care behavior, and high socio economic status. [Penel Gizi Makan 2005,28(2): 56-65] Keywords: posyandu, weighing coverage